LEVEL OF KNOWLEDGE AND BEHAVIOR OF SMOKING HABITS ON THE INCIDENCE OF PULMONARY TB PATIENTS - Toto Harto; Roni Ferdi; Miti Kartika; Muhammad Hasan Azhari (Majalah Kedokteran Sriwijaya, 2024)
Tuberculosis is often referred to as the great imitator, a disease that has many similarities with other diseases that also give common symptoms such as weakness and fever. In people with good immunity, the TB germs in their bodies will not be active or are in a state of sleep. Due to the lack of public awareness on how to deal with tuberculosis, many people are still affected by pulmonary TB. One of the factors affecting pulmonary tuberculosis is knowledge and smoking behavior. This study used an analytic survey method with a cross-sectional approach. Sampling was conducted when respondents happened to be present or available at the research location. This study involved 32 respondents. Analysis. The results showed that there was a significant relationship between the level of knowledge and smoking behavior and the incidence of pulmonary TB, with a p value of 0.020 each. It is hoped that further research will examine the number of cigarettes consumed by patients with a level of knowledge about the adverse effects of smoking on patients with pulmonary tuberculosis.